Benchmark Study of FINETM/Marine CFD Code for the Calculation of Ship Resistance - Firdhaus, Ahmad; Suastika, I Ketut; Kiryanto, Kiryanto; Samuel, Samuel (Department of Naval Architecture - Diponegoro University, 2021)
Benchmarking can be used to test CFD programs for selecting turbulence models, grid dependency studies, testing different numerical schemes and source codes, and testing different boundary conditions. CFD simulation in this study uses FINEâ„¢/Marine 7.2-1 software. The solver process at NUMECA uses the ISIS-CFD flow solver developed by EMN, which uses the incompressible unsteady Reynolds-average Navier stoke equation (RANSE). The solver is based on the finite volume method, and Turbulence models use SST k-Ï‰ models. The free surface flow around a model surface ship (DTMB 5415) advancing in calm water under steady conditions is numerically simulated. The geometry of the DTMB 5415 ship hull was provided in igs file format. The 1996 International Towing Tank Conference has recommended the DTMB 5415 combatant as a benchmark case for CFD computations of ship resistance and propulsion. The results compare well with the available experimental data. They allow an understanding of the differences that can be expected from vicious and potential flow methods due to their different mathematical formulations. It is demonstrated that the complementary application of these methods allows good predictions of the total ship resistance.